2015
DOI: 10.1186/s12871-015-0154-1
|View full text |Cite
|
Sign up to set email alerts
|

Esmolol reduces anesthetic requirements thereby facilitating early extubation; a prospective controlled study in patients undergoing intracranial surgery

Abstract: BackgroundAdequate cerebral perfusion pressure with quick and smooth emergence from anesthesia is a major concern of the neuroanesthesiologist. Anesthesia techniques that minimize anesthetic requirements and their effects may be beneficial. Esmolol, a short acting hyperselective β-adrenergic blocker is effective in blunting adrenergic response to several perioperative stimuli and so it might interfere in the effect of the anesthetic drugs on the brain. This study was designed to investigate the effect of esmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
1
11
0
3
Order By: Relevance
“…Esmolol combined with propofol or sevoflurane can inhibit the intubation reaction and reduce the amount of propofol or sevoflurane administered, which is conducive to smooth and rapid recovery after surgery. 23 However, there is still a risk of bradycardia; about 30% of patients may have transient bradycardia 24 or the depth of anesthesia may be affected, resulting in shallow anesthesia. The above-mentioned adverse conditions did not occur in this study, but this may be because of the small sample size or the good heart function in the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Esmolol combined with propofol or sevoflurane can inhibit the intubation reaction and reduce the amount of propofol or sevoflurane administered, which is conducive to smooth and rapid recovery after surgery. 23 However, there is still a risk of bradycardia; about 30% of patients may have transient bradycardia 24 or the depth of anesthesia may be affected, resulting in shallow anesthesia. The above-mentioned adverse conditions did not occur in this study, but this may be because of the small sample size or the good heart function in the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Beta-agonists increase wakefulness and excitation by activating the reticular activating system in the brain, [30] in turn reducing cortical arousal, which is how esmolol reduces agitation. [30,31] Several studies found that esmolol reduced the need for analgesics and sedatives, but most researchers have reported that esmolol is more effective when combined with other drugs than when administered as monotherapy. [10,22,32,33] For this reason, we combined esmolol with lidocaine, which relieves sore throat.…”
Section: Discussionmentioning
confidence: 99%
“…Strabismus surgery in children is known to cause minimal pain, [25,34] so we attempted to determine whether injection of lidocaine can reduce agitation by attenuating stimulation of the airway. And also, we predicted that because esmolol not only maintains hemodynamic stability but also suppresses wakefulness, [30] using the two agents in combination would achieve a greater reduction in agitation. Therefore, we compared an EL group with a lidocaine group, and found that only the patients in the EL group had a statistically significant reduction in agitation.…”
Section: Discussionmentioning
confidence: 99%
“…Hayvan modellerinde, GH seviyesi ile ilişkili olarak distal tübüller içerisine sodyum retansiyonu olduğu gösterilmiştir7. Ayrıca akromegalide aldosteron sentezi ve aldosterona duyarlılığın arttığı, yüksek IGF seviyelerinin aynı zamanda arterioler kalınlaşmaya da neden olduğu bilinmektedir [8][9] . Colao ve arkadaşları akromegalik olgularda ana karotid arterde intima-media kalınlığının (IMT) aynı yaşdaki gönüllülerden daha fazla olduğunu (1.04 mm -0.8 mm) vurgulamışlardır 9 .…”
Section: Discussionunclassified